A Parallel Corpus-Based Study of Collocations from English to Persian: Criticism, and Resolution - Mehrnoosh Pirhayati (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2021)
Since, translation was known and identified as a science, by James. S. Holmes in 1994, under the title of “Translation Studies”, its cruciality was revealed and so, more was taken into account by the scholars of this field. Based on him, translation is not just the act of converting words by considering the token of equivalence, but the action that different factors such as, politics, religion, culture, and the like can affect and control it. In fact, from one context to another context, such these meta-textual factors can be different in comparison to each other, or even can be completely in contrast with each other, and consequently can be the causes of particular production as the original text and its translation that can be regarded as it has differences or it is completely different to its original. On the other hand, collocations, as the items that are frequently brought together, are more in the danger of mistranslation. In this regard, this research as comparative, critical, and qualitative corpus-based study was stablished, in order to explore the bad Persian translations performed on the English collocational items, based on the factors of biasness, ideology and power, lack of the skill of coinage, lack of the knowledge of translation strategies like, calque, superficial translation, transliteration, etc…, lack of the knowledge of source/target collocational item/lack of the knowledge of source/target linguistic norm, and lack of target linguistics knowledge, and to present resolutions. To do so, different English materials from different fields were gathered which can be categorized into general English language (GEL), medicine, law, economics and commerce, politics and news, literature, religion, sport, advertisement, engineering, and art, which were translated after the Islamic revolution of Iran. This study benefited from Pirhayati’s (2019) model of TQA and TC and frameworks, and also considered Wouden’s (2004) definition of collocation and Lewis’s (2000) categories of collocational items. Those who may benefit from this research are translation students, translators, and the scholars of TS and language.